Dead girls dancing - Masterton, Graham (Masterton, Graham. Katie Maguire series., 2017)
In the middle of Cork, in the middle of the day, a fire blazes in a local dance studio. Thirteen women, all promising stars, die in the flames. Their young lives cut short by a tragic accident. But where others see tragedy, DCI Katie Maguire sees murder. This is not the first fire to sweep through Cork. And in one previous case, the victims were dead before the fire was started. As Katie Maguire investigates the strange, obsessive world of competitive Irish folk dancing, she must face her most chilling killer yet...